KAJIAN RUMAH GABA-GABA DI PERKOTAAN MERAUKE - Yashinta Irma Pratami Hematang; Mukhlis Alahudin; Diana S Susanti (Universitas Muhammadiyah Jakarta, 2022)
ABSTRAK. Merauke sebagai kabupaten terujung timur dari wilayah NKRI, selain dikenal dengan area perbatasannya juga menghasilkan tanaman sagu (Metroxylon sp.). Bagian dari tanaman sagu yaitu pelepahnya kemudian dimanfaatkan oleh masyarakat setempat menjadi material penyusun dinding rumah. Berdasarkan hasil wawancara, rumah ini selanjutnya dikenal masyarakat Merauke dengan sebutan Rumah Gaba-Gaba. Penerapan Rumah Gaba-Gaba bukan hanya ada di daerah perkotaan tetapi dijumpai juga di daerah lain seperti pedalaman di sekitar Distrik Merauke. Untuk di daerah kota, Rumah gaba-gaba semakin berkurang. Pembelajaran detail sambungan kontruksi gaba-gaba di bangku perkuliahan jurusan bangunan (arsitektur dan teknik sipil) juga sekolah menengah kejuruan bidang teknik bangunan juga tida dijumpai. Penelitian ini kemudian bertujuan melihat bagaimana detail sambungan pelepah sagu pada dinding Rumah Gaba-Gaba di perkotaan Merauke serta menemukan bagaimana potensi dan tantangan pelestarian Rumah Gaba-Gaba dalam kaitannya dengan akses memperoleh material sagu di daerah perkotaan. Penelitian ini menggunakan metode penelitian kualitatif, jenis metode yaitu observasi terlibat dan pengambilan data ethnografis. Teknik pengambilan data secara tidak acak, teknik purposive sampling. Observasi/pengamatan dan wawancara dengan teknik penyajian data yaitu dengan verbatim. Hasil penelitian ini adalah gambar sambungan dinding pelepah sagu dimana terdapat kayu list ukuran 2/2 mengapit gaba-gaba, antar gaba disambung dengan tusukan bambu (seperti tusukan sate) dengan jarak antar tusukan adalah tidak saling sejajar secara vertikal dan juga kajian potensi dan tantangan pelestarian rumah material sagu area perkotaan Merauke. Kata kunci: pelepah sagu, dinding, material lokal ABSTRACT. Merauke, the easternmost district of the Republic of Indonesia, besides being known for its border area, also produces Metroxylon sp., the sago plants. Part of the sago plant, namely sago midrib, is then used by the local community to become the building material for the walls of the houses. Based on the interview results, information was obtained that this house was later known as Rumah Gaba-Gaba. The application of Rumah Gaba-Gaba exists in urban areas and can also be found in other areas such as the rural around Merauke District. The application of Rumah Gaba-Gaba exists in urban areas and can also be found in other areas such as the rural around Merauke District. However, it is found that the application of Gaba-Gaba wall construction is decreasing in urban areas. Then learning the details of this construction in the lectures majoring in building (architecture and civil engineering) and vocational high schools in building engineering is not there. This research then aims to see how the details of the connection of the sago midrib on the walls of the Rumah Gaba-Gaba in Merauke city and find out how the potencies and challenges of preserving the Rumah are preserved Gaba-Gaba are related to access to sago material in urban areas. This research uses qualitative research methods. The types of methods are involved observation and ethnographic data collection. The collecting data is not a random, purposive sampling technique—observations and interviews with data presentation techniques, namely verbatim. The results of this study are a picture of the connection of the Gaba-Gaba wall where there is a list of 2/2 size wood flanking the Gaba-Gaba. Between the Gaba is connected with a bamboo puncture (such as a satay puncture). The distance between the punctures is not parallel to each other vertically. It is also a study of the potential and challenges for the conservation of sago material houses for the urban area of Merauke.Keywords: sago midrib, wall, local material